1985
DOI: 10.1175/1520-0477(1985)066<0505:psasc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Project STORMFURY: A Scientific Chronicle 1962–1983

Abstract: Between 1962 and 1983, research in hurricane modification centered on an ambitious experimental program, Project STORMFURY. The proposed modification technique involved artificial stimulation of convection outside the eye wall through seeding with silver iodide. The artificially invigorated convection, it was argued, would compete with the convection in the original eye wall, lead to reformation of the eye wall at larger radius, and thus produce a decrease in the maximum wind. Since a hurricane's destructive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 32 publications
1
37
0
3
Order By: Relevance
“…While there is now a good understanding of particle properties that affect CCN activation, there is still a lack of understanding as to which intrinsic properties of aerosol particles determine their ice nucleation capabilities (Szyrmer and Zawadzki 1997;Cantrell and Heymsfield 2005). While ice nucleation was studied intensely in the 1970s in the scope of weather modification programs (Bruintjes 1999;Federer et al 1986;Willoughby et al 1985), contem-porary interest focuses more on the climate impact of natural and anthropogenic ice nuclei through the so-called aerosol indirect effect. The indirect effect traditionally refers to an increase in cloud droplets due to anthropogenic aerosols (Baker 1997).…”
Section: Introductionmentioning
confidence: 99%
“…While there is now a good understanding of particle properties that affect CCN activation, there is still a lack of understanding as to which intrinsic properties of aerosol particles determine their ice nucleation capabilities (Szyrmer and Zawadzki 1997;Cantrell and Heymsfield 2005). While ice nucleation was studied intensely in the 1970s in the scope of weather modification programs (Bruintjes 1999;Federer et al 1986;Willoughby et al 1985), contem-porary interest focuses more on the climate impact of natural and anthropogenic ice nuclei through the so-called aerosol indirect effect. The indirect effect traditionally refers to an increase in cloud droplets due to anthropogenic aerosols (Baker 1997).…”
Section: Introductionmentioning
confidence: 99%
“…1E) was addressed by glaciogenic cloud seeding. Hurricane mitigation was first attempted between 1962 and 1983 in the framework of project STORMFURY by the US government (Willoughby et al, 1985). The envisioned modification technique involved artificial stimulation of convection at the outer periphery of the eyewall through seeding of strong convective cloud towers with silver iodide for the purpose of freezing super-cooled water (water in liquid state but colder than 0 • C).…”
Section: Introductionmentioning
confidence: 99%
“…Although the maximum winds of some of the seeded TCs decreased, the change in hurricane intensity was attributed to natural intensity fluctuations rather than to seeding. The analysis of the microphysical structure of tropical convective (TC) clouds (Willoughby et al, 1985) showed that at the levels where seeding was applied there was too little supercooled water and a significant amount of cloud ice. Consequently, the glaciogenic seeding was not likely to affect cloud dynamics, at least in the way assumed in the STORMFURY conceptual model.…”
Section: Introductionmentioning
confidence: 99%
“…The cloud-seeding approach ultimately proved ineffective (3,4). Many strong, mature tropical cyclones exhibit a natural "eyewall replacement" process (5) in which a new (outer) eyewall takes over from the original (inner) eyewall, just as had been hypothesized-but with no cloud seeding taking place.…”
mentioning
confidence: 99%